The Effect of Environmental Costs and Capital Structure Against Profitability at UD Sederhana - Widuta, Venesia; Frenky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether environmental costs and capital structure have a significant effect on profitability at UD Sederhana. This study uses quantitative data method and the data source is secondary data. The population in this study includes data in 48 months. The sample in this study used the entire population using saturated sample data collection techniques. Data analysis and testing consists of descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (T test) and simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study indicate that environmental costs has a significant effect on profitability with a calculated T-count of 5,625 > T-table 2,012. Capital structure does not have a significant effect on profitability with a calculated T-count of -0,216 < T-table 2,012. Environmental costs and capital structure have a significant effect on profitability with a calculated F-count of 15,827 > F-table of 3,20 and a regression coefficient value of 41,3%.